Software Development of Speed Typing Counter Application as a Typing Lesson Supporting Tool - Widodo, Yusac Ismail Fauzi; Yuana, Rosihan Ari; Maryono, Dwi (IJIE (Indonesian Journal of Informatics Education), 2017)
This research aims to design and create media applications that will be used to train the speed and accuracy of typing in the classroom. Lack of instructional media typing speed appropriate to the circumstances in the classroom was the background of this research. The study began with the observation phase, then followed by system design and coding. An application as the research results has main features: the study materials, practice typing, and data management, which each function is executed by the user level use. Implementation of the user level is intended to secure the data from unauthorized third parties so that only students and teachers can see the results of learning. Furthermore, the application also gives teachers the opportunity to participate in learning, a way to create and change the questions used for the exercise. As a typing progress report, the application can also display the results in various formats such as speed tables, accuracy tables, speed graph, and chart accuracy. This work is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.